New Records of Proceratium deelemani Perrault, 1981 (Hymenoptera : Formicidae : Proceratiinae) in Sumatra - Rini Wulandari; Dwi Hilda Putri; Dezi Handayani; Afifatul Achyar; Rijal Satria (Bioscience, 2024)
Proceratium Roger, 1863 is a genus of ants that has widely distributed throughout the world, Proceratium species rarely collected, their cryptobiotic lifestyle. This condition also occurs on the Sumatra Island, Indonesia. So far, only single species was recorded in this island, namely Proceratium papuanum Emery, 1897. We conducted a survey of leaf-litter ants in June 2021 by using Winkler’s extraction method in lowland disturbed forest near Tiga Tingkat Water fall Lubuk Hitam, Teluk Kabung Utara, Bungus Teluk Kabung, Padang, West Sumatra, Indonesia. The discovery of Proceratium deelemani Perrault, 1981 for the first time in Sumatera Island, Indonesia was increased the total ant fauna in this island. In the present study, we reports new distribution record of Proceratium deelemani Perrault, 1981 in Sumatra. Total two species of this genus was recorded in Sumatra: Proceratium deelemani Perrault, 1981 and Proceratium papuanum Emery, 1897.